2002
DOI: 10.1063/1.1429658
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical study of Cu–Au nanoalloy clusters using a genetic algorithm

Abstract: A study has been made of the structures and stabilities of copper and gold clusters and copper–gold nanoalloy clusters, with up to 56 atoms, modeled by the many-body Gupta potential. For pure copper clusters, the lowest energy structures are found to be based on icosahedral packing, while pure gold clusters tend to form less symmetrical (often amorphous) structures. In a number of cases, the replacement of a single gold atom by copper is found to be sufficient to convert the structure to that of the more symme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
325
5
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 369 publications
(352 citation statements)
references
References 46 publications
20
325
5
2
Order By: Relevance
“…These results can be compared with the genetic algorithm study on copper clusters by Darby et al [26], using Gupta potential. In agreement with the present study, Darby et al found that most of the clusters in this regime adopt structures based on icosahedron.…”
Section: A Geometry Optimizationmentioning
confidence: 99%
See 2 more Smart Citations
“…These results can be compared with the genetic algorithm study on copper clusters by Darby et al [26], using Gupta potential. In agreement with the present study, Darby et al found that most of the clusters in this regime adopt structures based on icosahedron.…”
Section: A Geometry Optimizationmentioning
confidence: 99%
“…They also found exceptions to the icosahedral growth at around Cu 40 , where the structures adopt decahedron like geometries (exact numbers are not available in the Ref. [26]). But the present study disagree with the genetic algorithm study in two points.…”
Section: A Geometry Optimizationmentioning
confidence: 99%
See 1 more Smart Citation
“…При этом, объектами пристального внимания как с практической, так и с академической точек зрения являются металлические кластеры [3]. Среди посвященных им исследований существует много работ по изучению пар компонен-тов кластеров Cu−Au [4][5][6] и Ni−Al [7,8]. Их форма, атомная структура, композиция и сегрегационные свой-ства являются объектами исследования, поскольку они влияют на химическую активность и каталитические свойства [9,10].…”
Section: Introductionunclassified
“…It should be noted that, even in the current state of the art in the development of highperformance computers, an ab initio simulation of this system remains impossible [2][3][4].…”
Section: Molecular Dynamic Potentialmentioning
confidence: 99%